Biomass and Carbon Content in Mangrove Tree, Mengkapan Village, Sei Apit Subdistrict, Siak Regency, Riau - Rasoel Hamidy (ECOTONE, 2020)
The mangrove forest area is an ecosystem with highly productive, with a carbon production rate balanced by tropical wet forests. Global warming is increasingly felt by the world's population which is characterized by global climate change. The obvious impact is greatly felt by rising sea levels. This study aims to determine the total surface biomass and carbon stored in mangroves in Mengkapan village, Sungai Apit Sub-district, Siak Regency, Riau. The method used is a 10 x 10 m square block, making 5 transect lines along the coastline and 5 transect lines along the river line. The results of the study found 10 types of mangroves that make up the study area with calculations of the number of mangrove stands found 3236 stands/ha with a total biomass of 61732.74 and carbon absorption of 113.18 tons C/ha.